Relative performance of sesame (Sesamum indicum) under organic, inorganic and integrated nutrient management - VERMA, SUNITA; SINGH, HAR VIR; SAXENA, RANI (The Indian Journal of Agricultural Sciences, 2013)
The experiments were carried out during kharif season in 2009–10 and 2010–11. The study comprised 8 treatment combinations consisting with different nutrient management, viz. T1, Control; T2, 100% RDF (Recommended dose of fertilizers-60 kg N + 40 kg P2O5 + 20 kg K2O/ha); T3, 50% RDF + 50% N through FYM (Farmyard manure); T4, 100% Recommended N through FYM; T5, 50% RDF + 50% N through VC (Vermicompost); T6, 100% recommended N through VC; T7, 50% RDF + 50% N through NOC (Neem oil cake); T8, 100% recommended N through NOC were tested in a randomized block design with three replications and two varieties Gujrat Til 2 and TKG 22. The LAI values were higher at later stage of growth (60 DAS) than early stage (30 DAS) under all treatments in both the years. At 90 DAS, the crop growth rate was maximum (5.40 g/m2/day) with T4 and T7 treatment during both the years. At 90 DAS, RGR was maximum (8.13 mg/g/day in 2009–10 and 8.20 mg/g/day in 2010–11 ) with T4 treatment. The seed yield was maximum (810 kg/ha in 2009-10 and 757 kg/ha in 2010–11) with the application of 100% recommended dose of fertilizers (T2). While the straw yield was maximum (4 650 kg/ha in 2009–10 and 4 497 kg/ha in 2010–11) in 100% recommended dose of fertilizers (T2). Application of 100% RDF through inorganics, recorded highest seed and straw yields which were at par to those recorded with application of 50% RDF + 50% N through NOC, 50% RDF + 50% N through VC and 50% RDF + 50% N through FYM. Application of full quantity of nutrients through organics, viz. NOC/VC/FYM produced lesser yields than 100% inorganic and other integrated nutrient management. The maximum NUE value was observed with application of 100% RDF through inorganic sources (88.37% in 2009–10 and 84.66% in 2010–11).The cost of cultivation was maximum (Rupees. 14 283/ha in 2009–10 and rupees.17 675/ha in 2010–11) under T6 (100% recommended N through VC). The benefit-cost (B:C) ratio was significantly maximum (2.27 in 2009–10 and 2.14 in 2010–11) in T2 (100% RDF) among all treatments.